PENGARUH CARA PENGOLAHAN DAN WAKTU BERBEDA TERHADAP KADAR PROTEIN DAGING BEKICOT (ACHANTINA FULICA) SEBAGAI SUMBER PROTEIN ALTERNATIF MASYARAKAT NEGERI LESLURU KECAMATAN TEON NILA SERUA (TNS) WAIPIA - Rofli J Lessu; Mery Pattipeilohy; Stevin Melay (BIOPENDIX, 2019)
Background: Snail (Achantina fulica) is one of the animals from the gastropod class. Snails are often consumed by the Lesluru people as an alternative source of protein for fish substitutes. This study aims to determine the levels of snail meat protein which is processed by boiling, fumigation and frying, as well as providing information on the nutritional content of snails for the community in general. Method: The type of research used is experimental research and to test the protein content using the kjeldhal method. This research was conducted from November 4 to November 12, 2018. Results: This study was analyzed using the normality test, homogeneity test and followed by ANOVA test. In analyzing the data used the SPSS Windows version 16.0 program help. The results of the analysis of protein content of snail meat, known, the highest levels found in the treatment by fumigation with an average protein content of 40.4% while the lowest protein content found in boiling processing with an average protein content of 27.0%. Conclusion: treatment by fumigation while the lowest protein content is found in the treatment by boiling.